INTERFRAME VIDEO FORGERY DETECTION AND LOCALIZATION USING HISTOGRAM-ORIENTED GRADIENTS FOR SURVEILLANCE VIDEOS - J, Liba Manopriya (INFOCOMP Journal of Computer Science, 2023)
. Surveillance cameras are generally used in real-time scenarios to provide assurance and security. These videos often serve as crucial evidence in court proceedings. Currently, technology is growing rapidly, resulting in the availability of various editing tools, which are essential for checking the integrity and trustworthiness of video content. Forgery detection is most commonly accomplished through pixel-correlation methods that take a long time to calculate since each pixel of a video frame is compared to identify a forgery. So, the statistical value-based histogram approach effectively detected inter-frame forgeries such as frame insertion, deletion, and duplication. This paper proposes a method to detect forged videos using Histograms of Gradients (HOG) with Discrete Wavelet Transform (DWT). The experimental outcome suggests that the proposed method is more accurate than the existing method and gives a 0.98 accuracy score with a faster execution time.